Interaction between RME-based blended learning and self-regulated learning in improving mathematical literacy - Novita Sari; Zuli Nuraeni; Novika Sukmaningthias (Jurnal Elemen, 2022)
Most prior studies on mathematical literacy (ML), self-regulated learning (SRL), and RME-based blended learning were carried out qualitatively. Therefore, it was necessary to test them with statistical inference. This study aimed to analyze the interaction between RME-based blended learning, conventional learning, and SRL in improving students' ML. The method used was quasi-experimental with a 2x2 factorial design. The population was students in grade 7 with a sample of 38 students (21 males and 17 females). RME-based blended learning was conducted in the experiment class, while conventional learning was in the control class. Self-regulated learning and mathematical literacy data were obtained from the questionnaire and test, respectively. Data were analyzed using the Adjusted Rank Transform Test with Two-Way ANOVA and Mann-Whitney U test. The result showed an interaction between RME-based blended learning, conventional learning, and SRL towards students' ML improvement. Students' ML improvement who received RME-based blended learning was higher than those who received conventional learning regarding the high level of SRL and vice versa at the low level. Furthermore, students' ML improvement with high SRL was slightly higher than those with low SRL after receiving RME-based blended learning and vice versa after getting conventional learning.